The persuasive effects of gestures in media discourse - Georget, Patrice (Universidad de Chile. Instituto de la Comunicación e Imagen, 2009)
We study the persuasive role of gestures in communication media, thanks to two empirical investigations that illustrate the active role of the receiver. First, we show which is the gesture role of a politician in the value allocation expressed by his audience. In a second investigation, we examine the gesture role depending on the type of heuristic versus systematic cognitive processing performed by the subjects. In this way, these results call into question the idea that the nonverbal is merely an index treating peripheral persuasive communication.